Measurement of the Vertical Spatial Metaphor of Power Concepts Using the Implicit Relational Assessment Procedure - Hong, Bao; Zhang, Lu; Sun, Hongri (Frontiers in Psychology, 2019)
This experimental study explored the use of the implicit relational assessment procedure (IRAP) for understanding the vertical spatial metaphor of power. In the classic IRAP procedure, we formed four sets of stimuli based on the relationship between power words (powerful and powerless words) and vertical position on a computer screen (upper or lower) that were either pro-metaphor (i.e., powerful-high, powerless-low) or anti-metaphor (i.e., powerful-low, powerless-high). Participants were then asked to judge whether the words were consistent or inconsistent with the set of instructions given to them. We found that the Dirap scores of powerful words in an above vertical space and powerless words in a below vertical space were higher than zero. Furthermore, the Dirap scores of the pro-metaphor stimuli were significantly greater than were those of the anti-metaphor stimuli. Vertical spatial position metaphor of power concepts was verified again by IRAP. These findings suggest that there is an established spatial metaphor for power, which we explain using relational frame theory. It is the first study to our knowledge to explore this metaphor using the IRAP, which overcomes the limitations of paradigms such as the implicit association test, and provides a better understanding of the mechanism of the metaphor.